Chaetoceros mitra ... - Li, Yang; Boonprakob, Atchaneey; Gaonkar, Chetan C.; Kooistra, Wiebe H. C. F.; Lange, Carina B.; Hernández-Becerril, David; Chen, Zuoyi; Moestrup, Øjvind; Lundholm, Nina (Zenodo, 2017)
Chaetoceros mitra This was the first species of the C. lorenzianus complex to be described, as Dicladia mitra from the Sea of Kamtschatka (Fig 20A) [17] based only on a valve of a resting spore. When chains of cells were found, the taxon was transferred to Chaetoceros [18]. Cleve described the cells as forming straight chains with narrow peanut-shaped to narrow elliptical apertures, concave valves and strong terminal setae diverging c. 90˚, and diverging from the apical plane (Brunel Group II) with spirally arranged puncta and indistinct transverse striations (Fig 20B and 20C) [18]. This agrees with our observations, except for the spiral arrangement of puncta. Cleve’s drawings (loc. cit. Fig 1C) show a pattern of spines or puncta on the spines similar to what we have seen (Fig 14A–14D), perhaps spirally inserted spines. Chaetoceros mitra can distinguished from all the other species of the complex by the sibling setae diverging 30˚–80˚ from the apical plane, defined as Brunel Group II (Fig 13A and 13B) ... : Published as part of Li, Yang, Boonprakob, Atchaneey, Gaonkar, Chetan C., Kooistra, Wiebe H. C. F., Lange, Carina B., Hernández-Becerril, David, Chen, Zuoyi, Moestrup, Øjvind & Lundholm, Nina, 2017, Diversity in the Globally Distributed Diatom Genus Chaetoceros (Bacillariophyceae): Three New Species from Warm-Temperate Waters, pp. 1-38 in PLoS ONE (e 0168887) (e 0168887) 12 (1) on page 30, DOI: 10.1371/journal.pone.0168887, http://zenodo.org/record/12827437 ...